Design an attendance system using Global Positioning System (GPS) technology at PT. Cipta Anugrah Musi - Muhammad Faisal (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The purpose of this research is to design an attendance system using Global Positioning System (GPS) technology, as a useful solution. At PT. Cipta Anugrah Musi for the marketing staff to still be able to do attendance without using a fingerprint attendance machine. Based on the results of research and discussion on the marketing employee attendance monitoring system in the form of this android mobile, the following conclusions can be drawn. From the black box testing that has been done, it can be concluded that the employee attendance monitoring system can run well and there are no problems. GPS technology can provide information on where to take employee photos so that it is easy to find out the position of the employee's absence at that time to avoid cheating in attendance.